2010
DOI: 10.1073/pnas.0906765107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical amplification by hair cells in the semicircular canals

Abstract: Sensory hair cells are the essential mechanotransducers of the inner ear, responsible not only for the transduction of sound and motion stimuli but also, remarkably, for nanomechanical amplification of sensory stimuli. Here we show that semicircular canal hair cells generate a mechanical nonlinearity in vivo that increases sensitivity to angular motion by amplification at low stimulus strengths. Sensitivity at high stimulus strengths is linear and shows no evidence of amplification. Results suggest that the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 63 publications
5
44
0
Order By: Relevance
“…Twitches have been observed in the vestibular cupulae of fishes and in the hair bundles of amphibians and reptiles including birds, but not in the bundles of the mammalian cochlea (6,17,18,21,22). Piscine, amphibian, and reptilian hair bundles can oscillate spontaneously, but autonomous oscillation of bundles from mammals has not been observed (3,5,23).…”
Section: Discussionmentioning
confidence: 97%
“…Twitches have been observed in the vestibular cupulae of fishes and in the hair bundles of amphibians and reptiles including birds, but not in the bundles of the mammalian cochlea (6,17,18,21,22). Piscine, amphibian, and reptilian hair bundles can oscillate spontaneously, but autonomous oscillation of bundles from mammals has not been observed (3,5,23).…”
Section: Discussionmentioning
confidence: 97%
“…Beyond cochlear mechanics, our findings have important implications for all sensory systems, which (with the exception of a few species of lizards) all contain accessory gelatinous structures overlying hair cells. Gels, such as the cupulae and otolithic membranes found in the vestibular system and those covering electrosensory hair cells on the skin of aquatic vertebrates, play a key role in hair cell stimulation (58)(59)(60). Much like the TM, these gels are poised to undergo deformations in response to transduction currents.…”
Section: Resultsmentioning
confidence: 99%
“…If this were also the case in hair cells, it is conceivable that the SO could change its dimensions and rigidity depending on variations in intracellular Ca 2+ concentration (with the latter regulated, in part, by the large subcuticular mitochondria), and thus influence hair bundle or cuticular plate movements, or tilting of the cell neck. Any of these actions could alter the sensitivity of the transduction apparatus, and thus, mechanotransduction (45). Rüsch and Thurm (46) showed that hair bundles at different sites on the sensory epithelium exhibit differences in amplitude and in the time course of deflection.…”
Section: Discussionmentioning
confidence: 99%
“…We used serial sections of chinchilla utricular macula for conventional TEM and for IVEM. Our TEM methods were described previously (45). We analyzed a total of 41 tomograms using research facilities at the National Center for Microscopy and Imaging Research.…”
Section: Methodsmentioning
confidence: 99%